Assessments measuring the perception of deficits in individuals with acquired brain injuries: a review of the literature - Forattore, Fernanda de Sousa; Ribeiro, Rafaela Larsen (Acta Fisiátrica, 2015)
Objective: Through a review of the literature, to select assessments measuring the perception of deficits of individuals with acquired brain injuries who have undergone a self-awareness intervention. Method: A review in the BIREME and PubMed databases was performed going over the past 10 years. Results: In this paper, eleven articles were selected that contained assessments of self-awareness before and after a therapeutic intervention and that had sampled individuals with diagnoses of traumatic brain injury (TBI), stroke, or cerebral tumor. Conclusion: A significant number of publications were found from Australia, European countries, and the United States. The instruments mostly used in the studies were the Self-awareness of Deficits Interview (SADI) and the Awareness Questionnaire (AQ). No validated and standardized studies or evaluations were found from Brazil. Thus, development, translation, and adaptation of assessments measuring the perception of awareness in the Brazilian population are required in order to provide an evidencebased practice by the use of intervention models